The watchman fell asleep : the surprise of Yom Kippur and its sources - Bar-Joseph, Uri (SUNY series in Israeli studies., 2005)
"Based on many formerly undisclosed intelligence and military documents, the secret protocols of discussions on the eve of the war, and interviews with relevant figures, The Watchman Fell Asleep is a compelling account of Israel's intelligence failure before the 1973 Arab attack known as the Yom Kippur War. The Hebrew version of this book was awarded the Tshetshik Prize for Strategic Studies on Israel's Security in 2001, and the Israeli Political Science Association's Best Book Award in 2002. Available here in English for the first time, Uri Bar-Joseph has crafted an authoritative explanation of the most traumatic event in Israel's stormy history and one of the biggest strategic military surprises of the twentieth century."--Jacket